2012
DOI: 10.1021/la3015404
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Template Effects That Control the Structure and Function of Nonspherical, Biotemplated Pd Nanomaterials

Abstract: Advances in nanotechnology have indicated that the passivant and the inorganic surface play a pivotal role in controlling the structure/function relationship of materials. Beyond standard materials-based methods, bioligands have recently demonstrated the production of unique nanomaterial morphologies for application under ambient conditions for multiple activities, such as catalysis and biosensing. We have recently demonstrated that a biotemplate technique could be employed to produce spherical and linear Pd n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…Comparing previous reports of rotavirus VP6, TMC-cys, M13, and synthetic peptides as bio-templates for the synthesis of Pd nanoparticles, the diameter of the particles, structure, crystallinity, and catalytic activity of the particles can be tuned depending of the Pd precursor, concentration, and reducing agent, and in some cases by the reaction temperature [9,14,16,19,38,39]. Our results of molecular docking also demonstrated that the high affinity residues on VP6 helped to Comparing previous reports of rotavirus VP6, TMC-cys, M13, and synthetic peptides as bio-templates for the synthesis of Pd nanoparticles, the diameter of the particles, structure, crystallinity, and catalytic activity of the particles can be tuned depending of the Pd precursor, concentration, and reducing agent, and in some cases by the reaction temperature [9,14,16,19,38,39]. Our results of molecular docking also demonstrated that the high affinity residues on VP6 helped to constrain the size and distribution of Pd particles all over the bio-template external surface.…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 74%
“…Comparing previous reports of rotavirus VP6, TMC-cys, M13, and synthetic peptides as bio-templates for the synthesis of Pd nanoparticles, the diameter of the particles, structure, crystallinity, and catalytic activity of the particles can be tuned depending of the Pd precursor, concentration, and reducing agent, and in some cases by the reaction temperature [9,14,16,19,38,39]. Our results of molecular docking also demonstrated that the high affinity residues on VP6 helped to Comparing previous reports of rotavirus VP6, TMC-cys, M13, and synthetic peptides as bio-templates for the synthesis of Pd nanoparticles, the diameter of the particles, structure, crystallinity, and catalytic activity of the particles can be tuned depending of the Pd precursor, concentration, and reducing agent, and in some cases by the reaction temperature [9,14,16,19,38,39]. Our results of molecular docking also demonstrated that the high affinity residues on VP6 helped to constrain the size and distribution of Pd particles all over the bio-template external surface.…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 74%
“…One of the strategies used for chemical transformations is catalytic reactions using transition metals. Various transition‐metal catalysts are useful for chemical transformations, and palladium (Pd) shows catalytic activity for a diverse range of cross‐coupling reactions, as well as hydrogenation, and π‐allyl substitution . The catalytic activities of nanosized Pd(0) catalysts are high because of the high surface‐to‐volume ratio .…”
Section: Introductionmentioning
confidence: 99%
“…Peptides, the secondary structures of proteins, have also been explored as scaffolds for crystal nucleation and growth, and they can be designed to self‐assemble into a large variety of structures ( Figure A–C). For example, self‐assembled peptide frameworks can generate linear, networked Pd materials (Figure A) . A self‐assembled, well‐ordered, flower‐like hierarchical dipeptide architecture can serve as a template for the synthesis of Au nanoflake films with remarkable surface‐enhanced Raman spectroscopy properties (Figure C) .…”
Section: Bioinspired Synthesis Via Bio‐macromolecule Regulationmentioning
confidence: 99%
“…A) Schematic diagram for networked Pd nanostructures formation using the peptide templates. Reproduced with permission . Copyright 2012, American Chemical Society.…”
Section: Bioinspired Synthesis Via Bio‐macromolecule Regulationmentioning
confidence: 99%